Is Declining malaria vector population in Africa a result of intervention Measures or sampling tools inefficiency? - Kweka, Eliningaya (Journal of Health & Biological Sciences, 2013)
Recent entomological surveys have shown a declining trend of malaria vector population in sub-Saharan Africa and the observation have beenassociated with the scale-up and intensive use of malaria intervention measures such as insecticides treated nets and insecticide residual sprays.However, little is known on the contribution of the mosquito sampling tools inefficiency on the declining trends of malaria vector population. Inthis commentary paper, we explore the possibility of contribution of mosquito sampling tools’ inefficiency to the observed declining trends ofmalaria vector population in Africa.